The Application of Pattern Recognition in Electrofacies Analysis - Huan Li; Xiao Yang; Wenhong Wei (Journal of Applied Mathematics)
Pattern recognition is an important analytical tool in electrofacies analysis. In this paper, we study several commonly used clustering and classification algorithms. On the basis of advantages and disadvantages of existing algorithms, we introduce the KMRIC algorithm, which improves initial centers of K-means. Also, we propose the AKM algorithm which automatically determines the number of clusters and apply support vector machine to classification. Finally, we apply these algorithms to electrofacies analysis, where the experiments on the real-world datasets are carried out to compare the merits of various algorithms.